Breaking the Brass Ceiling: Challenges and Opportunities for Women Leaders in Law Enforcement Agency - Etheldiana Lynn, Andotion; Surena, Sabil; Nur Fatihah, Abdullah Bandar; Zaiton, Hassan; Dayang Kartini, Abang Ibrahim (HRMAS, 2025)
Women remain underrepresented in leadership positions within law enforcement agencies, where institutional culture continues to be predominantly male-oriented. This study aims to examines the challenges encountered by women officers in advancing to leadership roles within law enforcement agencies. Using a qualitatively designed, in-depth interviews were conducted with ten women officers to explore their experiences and perceptions. The analysis identified three main challenges impeding women’s advancement: cultural and societal expectations, work-life balance constraint, and inadequate organisational support These factors collectively reflect the persistent influence of gendered norms and structural barriers in law enforcement contexts.. To promote gender equity, the study highlights the need for systematic interventions, including regular organisational audits, revised policies, mentorship programmes, training programmes and targeted leadership development initiatives. The findings further substantiate the applicability of Role Congruity Theory in explaining the gendered dynamics of leadership advancement within male-dominated institutions. This research contributes to the ongoing discourse on gender equity in law enforcement agencies and underscores the importance of institutional transformation to support women’s empowerment and equitable representation in leadership positions.